Measuring the Success of Ocean Capacity Initiatives - Maila Guilhon; Marjo Vierros; Harriet Harden-Davies; Diva Amon; Sergio Cambronero-Solano; Christine Gaebel; Kahlil Hassanali; Vanessa Lopes; Adam McCarthy; Andrei Polejack; Gail Sant; Julia Schutz Veiga; et al. (Oceanography, 2025)
The strengthening and enhancement of capacity are stated goals of several international ocean law and policy instruments that focus on biodiversity conservation, fisheries management, sustainable development, pollution, mineral extraction, traditional knowledge, and ocean science. Yet, achieving these goals has proved elusive, as illustrated by persisting divides in capacity and technology (Amon et al., 2022a; Bell et al., 2023). This has led to the emergence of new terminology, such as capacity sharing, which reflects the need for evolving practices away from unidirectional approaches and toward equitable partnerships (Harden-Davies et al., 2022) that recognize the value of existing knowledge (scientific or not), as well as practices and values held by a community (Spalding et al., 2023).